Bergamo and Covid-19: How the Dark Can Turn to Light - Perico, Norberto; Fagiuoli, Stefano; Di Marco, Fabiano; Laghi, Andrea; Cosentini, Roberto; Rizzi, Marco; Gianatti, Andrea; Rambaldi, Alessandro; Ruggenenti, Piero; La Vecchia, Carlo; Bertolini, Guido; Paglia, Stefano; et al. (Frontiers in Medicine, 2021)
The novel coronavirus, SARS-CoV-2, continues to spread rapidly. Here we discuss the dramatic situation created by COVID-19 in Italy, particularly in the province of Bergamo (the most severely affected in the first wave), as an example of how, in the face of an unprecedented tragedy, acting (albeit belatedly)—including imposing a very strict lockdown—can largely resolve the situation within approximately 2 months. The measures taken here ensured that Bergamo hospital, which was confronted with rapidly rising numbers of severely ill COVID-19 patients requiring hospitalization, was able to meet the initial challenges of the pandemic. We also report that local organization and, more important, the large natural immunity against SARS-CoV-2 of the Bergamo population developed during the first wave of the epidemic, can explain the limited number of new COVID-19 cases during the more recent second wave compared to the numbers in other areas of Lombardy. Furthermore, we highlight the importance of coordinating the easing of containment measures to avoid what is currently observed in other countries, especially in the United States, Latin American and India, where this approach has not been adopted, and a dramatic resurgence of COVID-19 cases and an increase in the number of hospitalisations and deaths have been reported.